Kegiatan Penyuluhan Hukum Tentang Perlindungan Konsumen Siswa Sekolah dalam Upaya Menjaga Kesehatan Terhadap Jajanan yang Beredar di Lingkungan Sekolah pada SMPN 154 Jakarta - Dwi Atmoko; Noviriska; Adhalia Septia Saputri; Sugeng; Heru Siswanto; Jantarda Mauli Hutagalung (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
Food availability and security is a basic human right. One group of people who often experience problems due to food poisoning are school children. Snacks play an important role in providing energy and other nutritional intake for school-aged children. School children's snacks that are not guaranteed to be healthy can potentially cause poisoning, digestive disorders and, if they last for a long time, can lead to poor nutritional status. Apart from that, unhealthy snacks can disrupt children's performance at school. Health education plays a role in changing a person's health behavior as a result of learning experiences. Therefore, it is necessary to hold outreach to provide additional knowledge to parents and children regarding the importance of choosing snacks. By knowing the characteristics of unhealthy snacks and the dangers of unhealthy snacks, it is hoped that parents can teach their children the characteristics of unhealthy snacks so that children do not buy unhealthy snacks. Apart from that, parents can bring supplies for their children, so that the food that enters the child's body is proven to be clean and healthy. In supporting the government program in providing education about healthy and nutritious food, knowledge is needed in the form of legal education regarding this matter. Knowledge about poisonous and unhealthy foods is conveyed to students so that they are wary of these foods or snacks. Therefore, sufficient cooperation and knowledge is needed from the school, especially teachers, regarding children's snack products at school that need to be paid attention to. So it is hoped that children's consumption of snacks can contribute energy and nutrients that are useful for growth